Enantiomeric selectivity in adsorption of chiral β-blockers on sludge. (July 2016) - Sanganyado, Edmond; Fu, Qiuguo; Gan, Jay
Abstract: Adsorption of weakly basic compounds by sludge is poorly understood, although it has important implications on the distribution and fate of such micropollutants in wastewater effluent and sludge. Additionally, many of these compounds are chiral, and it is likely that their interactions with sludge is stereoselective and that the process may be further modified by surfactants that coexist in these systems. Adsorption of (R) and (S)-enantiomers of five commonly used β-blockers, i.e., acebutolol, atenolol, metoprolol, pindolol and propranolol, on sludge was characterized through batch experiments. Stereoselectivity in adsorption increased with decreases in hydrophobicity of the β-blockers. The enantiomeric fraction (EF) of the amount of acebutolol, atenolol and metoprolol sorbed on sludge were 0.27, 0.55 and 0.32, respectively. Thus, K d values of the (S)-enantiomers of acebutolol and metoprolol were approximately twice that of the (R)-enantiomer, that is, 109 ± 11 and 57 ± 8 L/kg compared to 52 ± 13 and 22 ± 8 L/kg, respectively. There was no statistically significant difference in K d values of the enantiomers of pindolol and propranolol, suggesting stereoselectivity in adsorption was likely driven by specific polar interactions rather than hydrophobic interactions. The EF value of atenolol decreased from 0.55 ± 0.03 to 0.44 ± 0.04 after modifying the sludge with Triton X 100. These results suggested that surfactants altered adsorption of β-blockers to sludge, likely by forming ion pair complexes that promote hydrophobic interactions with the solid surfaces. Graphical abstract: Highlights: Sorption of β-blockers on sludge exhibit stereoselectivity. Stereoselectivity is observed when ionic interactions dominate sorptive behavior. Anionic surfactants increase sorption of β-blockers on sludge. Cationic and nonionic surfactants reduce stereoselectivity in sorption. Abstract : The adsorption of β-blockers on sludge exhibited stereoselectivity. Since toxicity of some β-blockers is stereoselective, the results help improving accuracy in risk assessment.